CAUSATION the basics. - Glennan, Stuart ([S.l.] : ROUTLEDGE, 2024)
Causation: The Basics explores questions about what causes are, and how we come to know them, describe them, and put them to use. The book begins with an introduction to the history of philosophical thinking about causation, followed by a series of chapters introducing important contemporary accounts of causation. It concludes with chapters on causation and agency, causal discovery, and causal explanation. Key questions explored in the book include: What distinguishes correlation from causation? How are the causes of singular events related to more general patterns of cause and effect? How are commonsense, scientific, and legal conceptions of causation related? Can certain occurrences be singled out as the main or principle causes of some effect? Is there a place in the world's causal structure for human agency and free will? While introducing the major philosophical debates about the nature of causation, Causation: The Basics emphasizes the uses and challenges of causal reasoning as it occurs in the sciences, engineering, medicine, and other areas of human life. With a glossary of key terms and suggestions for further reading, the book provides readers with a clear and concise introduction to both theoretical and practical questions about causation.
Keywords: Causation; PHILOSOPHY / General